Mathematical interpretation of mass transfer process in anaerobic bioreactors - Ружинская, Людмила Ивановна; Фоменкова, Анастасия Алексеевна (Eastern-European Journal of Enterprise Technologies, 2013)
The article considers the methanogenesis in bioreactors with immobilized microflora on fixed media. The processes of decomposition of organic pollution of the wastewater and the formation of metabolic products are analyzed. At the same time, the decomposition of organic pollution is considered from the standpoint of a two-stage process. As the first stage, the hydrolysis and acid production is considered, as the second - methanogenesis. On the basis of this process the spatial distribution of acid and methanogenic microorganisms in the anaerobic bioreactor has been suggested, and a model of mass transfer in a bioreactor has been built. As a calculated model, the motion of the fluid in the channel formed by sheets of biofilm carrier was taken. At the two-dimensional motion of a fluid in a channel, 2 types of the main substances mass transfer are considered, which are involved in the process of anaerobic digestion: by the convective diffusion in the core of the flow and by the molecular diffusion in the boundary wall layer and biofilm